Redefining the R1 resection for pancreatic ductal adenocarcinoma: tumour lymph nodal burden and lymph node ratio are the only prognostic factors associated with survival. Issue 9 (14th January 2013) - John, Biku J.; Naik, Prashant; Ironside, Alastair; Davidson, Brian R.; Fusai, Guiseppe; Gillmore, Roopinder; Watkins, Jennifer; Rahman, Sakhawat H.
Abstract Introduction The presence of positive nodal disease (LND) and the number of lymph nodes involved (LNB) are known to be significant prognostic markers for resected adenocarcinoma of the pancreas. In addition, the ratio of the number of involved nodes to the number of nodes resected known as the lymph node ratio (LNR) is emerging as an important prognostic marker. The role of the resection margin (RM) as presently defined (R1 ≤ 1 mm) is unclear as results differ based on the dataset. The aim of this study was to assess the impact of nodal disease and a redefined RM on outcome. Material and methods Retrospective analysis of pancreatic head resections for adenocarcinomas from 2003–2009. The RM was re‐analysed based on tumour clearance and categorized into: histopathological evidence of a tumour; ≤0.5 mm, ≤1 mm, ≤1.5 mm, or ≤2.0 mm of the actual surgical resection margin. The impact of histopathological variables on cancer‐specific survival (CSS) and disease‐free survival (DFS) was analysed. Results LND, LNB and LNR were independent prognostic markers for CSS (P = 0.048, 0.003, 0.016) but, did not influence DFS. A LNR < 0.143 was associated with a higher CSS [38.16 ± 4.69 versus 20.59 ± 2.20 months, P = 0.0042, hazard ratio (HR) 3.74 (95% confidence interval (CI) 1.52–9.23)]. An R1 RM was not associated with CSS or DFS on multivariate analysis, irrespective of the distance. LNB and LNR maintained independent significance irrespective of the size of the RM. Conclusion LNB and LNR are the only prognostic factors for CSS in patients with pancreatic head adenocarcinoma, but do not predict recurrence. Microscopic RMs does not seem to influence the outcome even when redefined. Further prospective studies are indicated to substantiate these findings.